1988
DOI: 10.1111/j.1460-2466.1988.tb02054.x
|View full text |Cite
|
Sign up to set email alerts
|

The Methods and Merits of Pornography Research

Abstract: We read with dismay the recent exchange between Christensen and Zillmann and Bryant on the effects of pornography (Journal of Communication, Winter 1987, pp. 186-188). First, we are disturbed by the tone of the exchange. We find it disrespectful to both parties and to ourselves. Second, we are disturbed that the debate appears to have ended with the findings of a single study conducted in our laboratory assuming paramount importance in answering the question of whether or not prolonged consumption of pornogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Donnerstein, whose work is frequently cited as evidence of pornography's negative social impacts, has repeatedly stressed that sexually explicit films have undesirable effects only when the sex is mixed with violence (7,15). Other scholars dispute this reading of the evidence and also raise methodological questions about various effects studies (e.g., 1, 4, 5, 8,12,19,20,21,22,23,24). Fueling the debate are the different interpretations of research findings made by those who advocate various theoretical models of pornography's functions and effects (13).…”
mentioning
confidence: 99%
“…Donnerstein, whose work is frequently cited as evidence of pornography's negative social impacts, has repeatedly stressed that sexually explicit films have undesirable effects only when the sex is mixed with violence (7,15). Other scholars dispute this reading of the evidence and also raise methodological questions about various effects studies (e.g., 1, 4, 5, 8,12,19,20,21,22,23,24). Fueling the debate are the different interpretations of research findings made by those who advocate various theoretical models of pornography's functions and effects (13).…”
mentioning
confidence: 99%
“…The HBS: the beam sampler is a hologram in engraved relief on a transparent substrate (silica) inducing forward diffraction. The birefringence of the HBS alone has been measured before its installation in the cavity system and the result is compatible with zero [12].…”
Section: Ellipsometer Componentsmentioning
confidence: 71%
“…The debates between researchers opposed to censorship and those whose studies demonstrated negative effects (and were perceived to be aligned with proponents of restrictions) were played out in the journal pages and sometimes reached a level of acrimony rarely seen on other issues (see Christensen, 1986Christensen, , 1987. A third type of reaction came from some of the social scientists prominent in the pornography research field who claimed misrepresentation of their data (Donnerstein, Linz & Penrod, 1987;Linz & Donnerstein, 1988). Researchers were harsh on their own methodological shortcomings, humble about their validity, headlining their pleas to limit effects to indirect ones (see Byrne & Kelley, 1989;Donnerstein, Linz & Penrod, 1987;Malamuth, 1986).…”
Section: Reaction/rom the Social Science Communitymentioning
confidence: 96%